Modeling calcium carbobate precipitation in the Acıgöl lake using aquatox - Karami, Fereshteh. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2017., 2017)
Due to the low costs of production processes, many industries use CaCO3 broadly as an inorganic mineral that appears in forms of limestone. The aim of this research is to model CaCO3 precipitation in the Ac gol Lake, using water quality data obtained from the eld measurements and meteorological data from the Turkish State Meteorological Service (TSMS) for the years 2013 and 2015. To achieve this aim, Environmental Protection Agency's (EPA) AQUATOX model is used to model the lake's water quality and CaCO3 precipitation. Firstly, a surrogate site is selected from AQUATOX library, which would represent the lake's characteristics in the best possible manner. The model is then calibrated for nine stations of the lake using parameters related to nutrients, plants, water quality, site characteristics, in ow loadings and lake hydrodynamics. Calibration dataset is obtained from eld measurements and meteorological data for the year 2013. Model validation is conducted both using data from the laboratory experiments carried out in 30 C, and eld observations obtained in August, 2015. Next, sensitivity of CaCO3 precipitation to the variations in major input parameters was assessed. Finally, scenario analysis was undertaken to investigate the e ect of meteorological changes on CaCO3 precipitation. Model results suggest that the amount of CaCO3 precipitation in the system ranges between 35.16 to 128.48 mg L{u100000}1d{u100000}1. The NRMSE between the modeled and observed values are found to be 0.41. Parameters related to primary productivity, especially those related with blue-greens are found to be the most signi cant parameters a ecting CaCO3 precipitation in the lake.
Keywords: Limestone -- Acıgöl Lake.; Water quality -- Acıgöl Lake.